Application of Lamaze Breathing Technique to Reduce Labour Pain in The First Stage Of Active Labour at Pelamonia Hospital Makassar - Kasim, Erna; Harun, Indriyani; Nurhayati, Nurhayati; Hafida, Ekayanti; Kessi, Andi Tenriola Fitri (LPPM STIKes Muhammadiyah Ciamis, 2025)
Labor pain is a common physiological response but often causes physical and emotional discomfort, especially in the first stage of active labor. One non-pharmacological method than can be used to reduce pain is the Lamaze breathing technique. This case study was conducted to determine the application of Lamaze breathing techniques on the reduction of pain during the active phase of the first stage of labour. a descriptive case study research methodology that focuses on one of the main issues in the selected case. Inclusion criteria: Mothers in active phase 1 labour with moderate to severe pain, mothers who are responsive or in good general condition with vital signs within normal limits, mothers under 35 years of age, primiparas/multiparas, mothers with cephalic presentation. Exclusion criteria: Mothers in active phase I labour with multiple pregnancies, malpresentation, haemorrhage, high-risk pregnancies accompanied by conditions such as pre-eclampsia, heart disease, asthma, premature rupture of membranes, pelvic abnormalities. The results show that both respondents experienced a decrease in pain intensity after applying the Lamaze breathing. The mothers appeared calmer, able to control their breathing, and reduced tension during contractions. The Lamaze breathing technique is effective in helping to reduce labor pain and is worth recommending as a non-pharmacological intervention.